Manajemen Pengelolaan Kelas Sebagai Alternatif Meningkatkan Kualitas Pembelajaran - Reksa Adya Pribadi; Arista Selly Maharani; Danu Dwi Arya; Retno Widati; Neng Kholilah Fitriyani (Jurnal Pendidikan Indonesia (JOUPI), 2023)
If all teachers carry out as explained by Ki Hajar Dewantara, there will be an increase in quality of learning. Learning to be of quality if in process changes occur in students which include cognitive, affective and psychomotor aspects. To cover these three aspects requires teacher expertise as a class manager.This research was conducted examine how classroom management strategies be implemented as alternative solution to improve quality learning in educational environment. By understanding important role of classroom management, this research also make a concrete contribution to development of more efficient learning methods. This research uses a qualitative method with phenomenological approach. Where the researcher collecting data by conducting observations and interviews to obtain information about essential phenomena from the participants experiences. Based on the results of interviews and observations linked to indicators and supporting theories, it can be concluded that the resource as the teacher already has good classroom management skills, she really pays attention for comfort of his students so that learning and teaching activities in the classroom run well. Then from the research it also be seen that there is commitment and sincerity from VI A class teacher in educating students and maintaining the quality of learning so that the quality of learning can improve..